The Immunological Mechanisms and Immune-Based Biomarkers of Drug-Induced Liver Injury - Liu, Wenhui; Zeng, Xiangchang; Liu, Yating; Liu, Jinfeng; Li, Chaopeng; Chen, Lulu; Chen, Hongying; Ouyang, Dongsheng (Frontiers in Pharmacology, 2021)
Drug-induced liver injury (DILI) has become one of the major challenges of drug safety all over the word. So far, about 1100 commonly used drugs including the regularly use of medications, illegal drugs, herbal products and/or dietary supplements, have been reported to induce liver injury, which also is the main cause of drug withdrawal from the pharmaceutical market and new drugs development interruption. Acute DILI may evolve into chronic DILI, or even worse, lead to life-threatening acute liver failure (ALF), the most common cause from DILI in Western countries. It generally considered to be closely related to genetic and environmental risk factors, through modification drug metabolism and/or excretion leading to a cascade of cellular events, including haptenization, immune response activation and a failure to adapt. Despite recent efforts on specific biomarkers about DILI are not still available for routine use in clinical practice, which makes the diagnosis of DILI uncertain and relying on the exclusion of other causes of liver disease. Here we review the underlying mechanisms of the immune response to DILI, and provide guidance for the future development of biomarkers for the early detection, prediction and diagnosis of DILI.